'Spain steals from us!' The 'populist drift' of Catalan regionalism. Issue 6 (November 2018) - Barrio, Astrid; Barberà, Oscar; Rodríguez-Teruel, Juan
Abstract This article analyses to what extent traditional mainstream Catalan regionalist parties and groups have adapted their discourses and collective performances in what might be seen as a 'populist drift' from regionalism to secessionism. This strategic move has been favoured by increasing party competition among these actors and would respond to the grievances reinforced by a context of austerity policies, political corruption, and a long institutional conflict on the centre–periphery. Our contribution is twofold. First, we show how parties and movements may combine regionalist and populist arguments in order to adapt their language, stressing the will of the Catalan people and its opposition against the Spanish political elites. Second, we explore how secessionist parties and groups have innovated their mobilization repertoires in order to fit with this populist-oriented discourse, employing mass mobilization, referenda simulations, and a populist political style in the institutions. Overall, Catalan secessionism presents a peculiar case where mainstream ruling parties adopt populist rhetoric and new mobilization practices to maintain power in adverse times.